First report of banana streak badnavirus in plantain landraces in southern Cameroon, Central Africa - Gauhl, F.; Pasberg-Gauhl, C.; Hughes, J.D.A. (Scientific Societies, 1997)
Banana streak badnavirus (BSV) has been reported from Musa spp. in many parts of West Africa, including Benin, Côte d'Ivoire, Ghana, and Nigeria (1). Symptoms of BSV infection in Musa spp. are sometimes similar to and confused with those caused by cucumber mosaic virus (CMV). BSV is prevalent in areas of southern Nigeria bordering Cameroon, and the disease may also be present in other Central African countries. In June 1996, six leaf samples with viruslike yellow/chlorotic streak symptoms were collected from plantain in the four villages, Awae, M'Balmayo, Nkolfep, and Nkolfoulou, within a 60-km radius of Yaoundé, Cameroon's capital. The samples were indexed for BSV and CMV by both triple antibody sandwich indirect enzyme-linked immunosorbent assay (TAS-ELISA) and immunosorbent electron microscopy (ISEM) to ascertain the presence of these two viruses. The TAS-ELISA was performed with rabbit polyclonal antiserum (obtained from B. E. L. Lockhart, University of Minnesota) for trapping and mouse polyclonal antiserum (obtained from G. Thottappilly, IITA) for detection. Out of the six samples, one tested strongly positive (>×2 A405 of the healthy control) and four were weakly positive (<×2 but >×1.5 A405 of the healthy control) for BSV by TAS-ELISA. However, all six samples contained BSV particles when examined by ISEM with rabbit polyclonal antiserum (from B. E. L. Lockhart) for trapping. None of the samples tested positive for CMV. These results confirm that BSV is present in Cameroon and that BSV is likely to be the causal agent of the symptoms.